A Systematic Approach of the Intrauterine Morphogenesis of the Human Palpebral Apparatus. (31st December 2022) - Munteanu, Octavian; Filipoiu, Florin-Mihail; Cirstoiu, Monica Mihaela; Bohiltea, Roxana Elena; Georgescu, Tiberiu Augustin; Dumitru, Adrian; Băloiu, Andra-Ioana; Publik, Mihai-Alin; Petrescu, Ioan-Andrei
ABSTRACT: The human eyelid embodies a vast diversity of functions. Acting as a protective shield for the ocular apparatus and as a light regulator in the sight process, eyelids stand a fascinating – yet omitted – role in facial aesthetics, serving as a racial trait by which humankind succeeded to manifest heterogeneity as a species. These assumptions are precisely forecasted right from in-utero life through intricate processes of growth and cell differentiation. In the Department of Anatomy of "Carol Davila" University of Medicine and Pharmacy, we performed morphological assessments on 41 embryos and fetuses with gestational ages ranging from 6 to 29 weeks. This study aims to illustrate the morphogenesis of eyelids in human embryos and fetuses and highlight macroscopic features which could potentially have significant clinical implications in ophthalmic pathology.